The effective theory of fluids at NLO and implications for dark energy - Ballesteros, Guillermo (Journal of cosmology and astroparticle physics, 2015)
We present the effective theory of fluids at next-to-leading order in derivatives, including an operator that has not been considered until now. The power-counting scheme and its connection with the propagation of phonon and metric fluctuations are emphasized. In a perturbed FLRW geometry the theory presents a set of features that make it very rich for modelling the acceleration of the Universe. These include anisotropic stress, a non-adiabatic speed of sound and modifications to the standard equations of vector and tensor modes. These effects are determined by an energy scale which controls the size of the high derivative terms and ensures that no instabilities appear.
Gesehen am 29.07.2020